Plant-Mediated Behavioural Avoidance of a Weevil Towards Its Biological Control Agent - Shields, Morgan W.; Wratten, Steve D.; Phillips, Craig B.; Van Koten, Chikako; Goldson, Stephen L. (Frontiers in Plant Science, 2022)
New Zealand pastures largely comprising Lolium ryegrass species (Poales: Poaceae) are worth $19.6B and are subject to major pest impacts. A very severe pest is the Argentine stem weevil Listronotus bonariensis (Kuschel) (Coleoptera: Curculionidae). This has been previously suppressed by the importation biological control agent, Microctonus hyperodae Loan (Hymenoptera: Braconidae). However, this suppression has recently declined and is subject to investigation. It has been hypothesised that grass type influences parasitism avoidance behaviour by the weevil and thus parasitism rates. This study explored the hypothesis using three common pasture grasses: A diploid L. perenne x L. multiflorum hybrid ryegrass (cv. Manawa), a tetraploid Italian ryegrass Lolium multiflorum Lam. (cv. Tama) and a diploid perennial ryegrass Lolium perenne L. (cv. Samson). The described laboratory-based microcosm methodology determined the extent of weevil avoidance behaviour on each of these three grasses when subjected to the parasitoid. Such reaction was gauged by the extent of reduced weevil on-plant presence and feeding compared to the control populations. In the absence of the parasitoid, the hybrid cv. Manawa ryegrass is as highly favoured by the weevil as the tetraploid cv. Tama. On diploid cv. Samson, feeding is considerably less. In the presence of the parasitoid, weevils on the tetraploid cv. Tama plants showed little avoidance activity in response to the parasitoid and it can be argued that the benefits of staying on this plant outweighed the possibility of parasitism. Conversely and surprisingly, in the parasitoid’s presence, weevils on diploid cv. Manawa showed very strong avoidance behaviour leading to levels of exposure similar to those found on the less-preferred diploid cv. Samson. These findings reflect how weevil parasitism rates have declined in most Lolium grasses, particularly diploids, since the 1990s but not in the tetraploid L. multiflorum. This contribution supports the hypothesis that the decline in weevil parasitism rates has been the result of rapid evolution arising from parasitoid-induced selection pressure and the countervailing effect of the nutritional quality of the host-plants.